Between Sport, Entertainment, and Gambling: Regulating Domino under Sharia-Based Qanun of Aceh - Faisal, Faisal; Anizar, Anizar; Nagara, Sabiya Puspa (Islamica: Jurnal Studi Keislaman, 2026)
This article examines the legal contestation surrounding me’en batee, the Acehnese term for domino, within Aceh’s Sharia-based local legal order. While me’en batee is often practiced as social entertainment, it is also associated with gambling, wasted time, public disorder, and neglect of religious obligations. The issue has become more complex as domino is increasingly framed as an organized sport when played without betting. Using normative juridical research with socio-legal sensitivity, this article analyzes statutory materials, Aceh’s qanun, Islamic legal concepts, academic literature, and selected public discourses. It argues that the problem of me’en batee is not a complete legal vacuum, since gambling and maysir are already regulated under national law and Qanun Aceh No. 6 of 2014. The main issue is normative ambiguity: how to distinguish entertainment, sport, and prohibited gambling. The article proposes a proportional qanun-based regulatory model that is preventive and regulatory rather than merely punitive, aiming to protect Sharia-based public order while avoiding overcriminalization.